Institutional quality and its role in accelerating the transition to renewable energy: A comparative study between fossil fuel-producing and non-producing countries in the Middle East and North Africa - BENMAMMAR, Abdelbasset; GHERBI, Nacer Salah Eddine; BENLEBBAD, Mohammed (The International tax journal, 2025)
This study examines the impact of institutional quality on the transition to renewable energy in 12 countries across the Middle East and North Africa (2000–2022) using a Panel-ARDL model. Long-term results reveal that non-oil economies outperform their their share of clean energy, driven by transparent governance and effective political stability, whereas oil-dependent economies face institutional constraints that hinder green investment. In the short term, the Error Correction Term (ECT) emerges as the sole statistically significant factor, underscoring the need for sustained institutional reforms to maintain momentum. The study recommends the introduction of specialized financing instruments (green bonds and investment funds) and the strengthening of accountability mechanisms to facilitate a fair and effective energy transition.